Distal Digital Nerve Repair Using Nerve Allograft With a Dermal Substitute: A Case Report - McKee, Desirae (Hand (N Y), 2019)
Background: Distal digital nerve repairs can present unique challenges for hand surgeons due to their sensitive location and ongoing difficulty obtaining soft tissue coverage in this region. Although autografts and nerve conduits have been shown to be of benefit with nerve gaps, they can have morbidities associated with their use. Nerve allografts have become a viable option over the past decade as their use has increased and data are now showing similar outcomes, particularly in short gap segments. Flaps and skin grafts are traditional coverage options for full thickness wounds but can pose challenges with multiple digit involvement, depth of wound, and critical structures exposed. Methods: We present a case where nerve allograft was used for distal digital nerve repair. Due to the distal nature of the nerve repair in the index digit distal to the trifurcation, the distal end of the nerve graft was connected to multiple small nerve ends. Dermal substitute was placed to achieve distal coverage of the affected digits. Results: At 6-month follow-up, the patient demonstrated improved strength, normal sensation, and full return of digital function. Conclusion: Nerve allograft can be used in combination with dermal skin substitute to achieve normal sensation and return of digital function following distal digital nerve injuries.